Supplementary conveyor system of two electric overhead line cars of mine - MA YUHUA; LIU YURONG; YU XIANGDONG; LI WENJUN; WANG BUKANG; HAO MINGRUI; NIAN KUI; ZHANG YANJUN; GUO ZHIJUN; YUAN XIAOMING; ZHANG SHENGDA; LIU ZHIGENG; et al. (2018)
The utility model belongs to the technical field of the colliery is the subsidiary transport of inclined shaft trolley -bus in the pit, specifically a supplementary conveyor system of two electric overhead line cars of mine. The problem of diesel oil trackless rubber -tyred car long distance heavy grade and tunnel pollute is solved, including power supply system, contact net, two electric vehicleand charging station, power supply system includes traction substation, feeder net and earth leakage protection, and traction substation installs on the contact net, and earth leakage protection is including leaking the insulating detection device of current detection device and gauze, and earth leakage protection is connected with the feeder net, installs in traction substation, the contact net includes and is equipped with electrified warning, and the contact net erects in the low gas of mine or does not have during gas assists the big lane of fortune, and ground and crossheading do not erect the contact net, two el